2011
DOI: 10.1111/j.1600-0412.2010.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium concentrations and metabolic variables in polycystic ovary syndrome

Abstract: Magnesium levels do not correspond with age, BMI, waist circumference, insulin sensitivity, glycemic levels, blood pressure, or lipid levels in reproductive-age women with PCOS. Magnesium concentrations are similar across PCOS phenotypes and indistinguishable from women without PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…These higher incidences could be explained by the fact that in that paper hypomagnesemia was defined as serum magnesium level below 1.8 mg/dl, in contrast to the present study in which 1.7 mg/dl was used as a cut-off to define hypomagnesemia. And indeed, if we re-analyze our data with a cut-off serum magnesium value of 1.8mg/dl, 15,1% of the entire population is diagnosed with hypomagnesemia: 11.5% of the overweight and obese patients and 32.6% of the patients with DM2, which is more in line with the Guerrero-Romero study and to studies performed in patients with DM2 (14% to 48%) [18][19][20]. Also, racial differences in serum magnesium levels have been reported.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These higher incidences could be explained by the fact that in that paper hypomagnesemia was defined as serum magnesium level below 1.8 mg/dl, in contrast to the present study in which 1.7 mg/dl was used as a cut-off to define hypomagnesemia. And indeed, if we re-analyze our data with a cut-off serum magnesium value of 1.8mg/dl, 15,1% of the entire population is diagnosed with hypomagnesemia: 11.5% of the overweight and obese patients and 32.6% of the patients with DM2, which is more in line with the Guerrero-Romero study and to studies performed in patients with DM2 (14% to 48%) [18][19][20]. Also, racial differences in serum magnesium levels have been reported.…”
Section: Discussionsupporting
confidence: 60%
“…This raises the question whether the relation between hypomagnesaemia and the higher HOMA-IR values exists independent of the excessive presence of VAT. In addition, hypomagnesaemia is the most frequent electrolyte disorder seen in T2DM patients as was also the case in our population [18][19][20]57], so the association between hypomagnesaemia and higher HOMA-IR might be purely related to the higher prevalence of T2DM in hypomagnesaemia patients. To clarify these associations, further research with a longitudinal set-up is definitely warranted.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Serum magnesium deficiency in this study may be secondary to decreased dietary magnesium intake as serum magnesium was positively related to dietary magnesium intake 9 . Studies among women with polycystic ovarian syndrome did not show any correlation between serum magnesium and insulin resistance [21][22] . This may be due to hormonal alteration in women with polycystic ovarian syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that serum magnesium concentrations are indistinguishable between women with and without PCOS, and that while PCOS patients were 19 times greater to have magnesium deficiency, no correlation was found between this decreased magnesium concentration and insulin resistance. After adjusting for calcium concentration, the relationship between magnesium and PCOS was insignificant [47] [48]. This suggests that calcium concentration is related to PCOS, however, which would affect the Ca 2+ /Mg 2+ ratio and thus cardiovascular risk factors.…”
Section: Pcosmentioning
confidence: 99%